DLK-dependent axonal mitochondrial fission drives degeneration after axotomy - Jorge Gómez-Deza; Matthew Nebiyou; Mor R. Alkaslasi; Francisco M. Nadal-Nicolás; Preethi Somasundaram; Anastasia L. Slavutsky; Wei Li; Michael E. Ward; Trent A. Watkins; Claire E. Le Pichon (Nature Communications)
Abstract Currently there are no effective treatments for an array of neurodegenerative disorders to a large part because cell-based models fail to recapitulate disease. Here we develop a reproducible human iPSC-based model where laser axotomy causes retrograde axon degeneration leading to neuronal cell death. Time-lapse confocal imaging revealed that damage triggers an apoptotic wave of mitochondrial fission proceeding from the site of injury to the soma. We demonstrate that this apoptotic wave is locally initiated in the axon by dual leucine zipper kinase (DLK). We find that mitochondrial fission and resultant cell death are entirely dependent on phosphorylation of dynamin related protein 1 (DRP1) downstream of DLK, revealing a mechanism by which DLK can drive apoptosis. Importantly, we show that CRISPR mediated Drp1 depletion protects mouse retinal ganglion neurons from degeneration after optic nerve crush. Our results provide a platform for studying degeneration of human neurons, pinpoint key early events in damage related neural death and provide potential focus for therapeutic intervention.